2008
DOI: 10.1038/sj.bjc.6604195
|View full text |Cite
|
Sign up to set email alerts
|

CYP1B1 expression is induced by docetaxel: effect on cell viability and drug resistance

Abstract: The cytochrome P450 CYP1B1 is consistently overexpressed in tumour cells as compared to their normal counterparts, but its precise role in drug resistance is yet to be defined. It has been reported that transfection of CYP1B1 results in increased resistance to docetaxel in V79 cells (McFadyen et al, 2001). In this study, we analysed changes in expression of CYP1B1 mRNA associated with pulse selection of MCF-7 cells with docetaxel. Docetaxel-selected MCF-7 cells (MCF-7 Txt), which showed increased resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 25 publications
(31 reference statements)
3
43
1
1
Order By: Relevance
“…The role of CYP1B1 in tumour suppression was also shown in a study where CYP1B1 null mice were protected against DMBA-induced tumours as compared with their wild-type counterparts (Buters et al, 1999). As CYP1B1 can inactivate the prostate cancer dug flutamide (Rochat et al, 2001) and is also induced in breast cancer cells after treatment with docetaxel (Martinez et al, 2008), it may have an important function in the development of resistance to chemotherapy. Overall, CYP1B1 has a variety of functions in both the treatment and development of breast cancer.…”
Section: Discussionmentioning
confidence: 96%
“…The role of CYP1B1 in tumour suppression was also shown in a study where CYP1B1 null mice were protected against DMBA-induced tumours as compared with their wild-type counterparts (Buters et al, 1999). As CYP1B1 can inactivate the prostate cancer dug flutamide (Rochat et al, 2001) and is also induced in breast cancer cells after treatment with docetaxel (Martinez et al, 2008), it may have an important function in the development of resistance to chemotherapy. Overall, CYP1B1 has a variety of functions in both the treatment and development of breast cancer.…”
Section: Discussionmentioning
confidence: 96%
“…We at first studied three relatively under-characterized genes identified in previous studies as potentially pertinent to docetaxel resistance. These included cytochrome P450 CYP1B1 that was shown to improve ability in cell survival in docetaxel resistant MCF-7 breast cancer cells 4 and was strongly induced by docetaxel in resistant PC-3 cells. We also reasoned that the persistent upregulation of Cyclin G 2 , the only cell cycle related gene detected in the docetaxel resistant PC-3 derivatives, might be also relevant to docetaxel resistance.…”
Section: Resultsmentioning
confidence: 99%
“…12 However CYP1B1 does not directly inactivate docetaxel and rather promotes cell survival. 4 Other studies determined that docetaxel was not metabolized by recombinant human CYP1B1 but binds to CYP1B1 to act as an effector of this enzyme. 13 Because shCYP1B1 silencing in 8B2 cells did not lead to measurable reduction in docetaxel resistance we concluded that CYP1B1 was not a key mediator of docetaxel resistance in our experimental model.…”
mentioning
confidence: 99%
“…Within this subset, we compared 26 ASXL1-mut to 39 ASXL1-wt patients and identified a signature of 92 differentially expressed probe sets, corresponding to 67 named genes (supplemental Table 4). Among the genes most strongly up-regulated in ASXL1-mut patients were LRP6 (a WNT signaling pathway coreceptor 30 ), cytochrome P450 CYP1B1 (associated with chemotherapy resistance 31 ), and gap junction protein ␣ 1 (GJA1, connexin 43). GJA1 couples early hematopoietic and stromal cells in the BM, is important for regeneration of hematopoiesis after chemotherapy, 32 and mediates secretion of stroma-derived factor 1 (CXCL12), a chemokine essential for hematopoietic stem cell homing and function.…”
Section: Analysis Of Gene-and Mir-expression Profiles Associated Withmentioning
confidence: 99%